Pengaruh Beban Kendaraan sebagai Beban Terbagi Rata terhadap Deformasi Geogrid sebagai Perkuatan Embankment - Adhe Noor Patria (Jenderal Soedirman University, 2012)
Soft soil such as clay was sensitive soil. Public contructions built in this kind of soil would face some problemssuch as long period consolidation time, unstable embankment slope, not easily compacted and high level settlement. Some solution that could be suggested were the usage of vertical drain, or the usage of geosynthetics material such as geogrid combined with floating piles.Analysis was carried out by using plaxis version 7.2. soil for embankment and embankment foundation was modelled in plane strain. Also geogrid andfloating piles were modelled in palne strain too. Surcharge load on top of embanknet were variated, they were 20, 35 and 50 kPa. The simulation was carried out in staged contruction mode.Final vertical displacement in geogrid due to 50 kPa vehicle load as surcharge load and long term load period (in this case excess pore water pressure was small) was -0,9062 m for rigid embankment and -1,4206 for interface embankment. The difference occured due to slip at the interface of geogrid and soil. It leaded to adding soil mass supportd by geogrid, furthermore the deflection of geogrid became bigger.